IDENTITY IN THE "POST-GLOBALIZATION" OF THE NEW SOCIETY AS "HOMO SPIRITUS IN UNIVERSUM CONCENTUS": EPISTEMOLOGICAL AND ONTOLOGICAL APPROACHES - Kharchenko, Julia (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Abstract. "Post-globalization" is presented as a new phenomenon, considered in the perspective of history, what actualized the definition of the place and role of the individual in the new state of society. The goal of the study was the conceptualization of the phenomenon of personality in the "post-globalization" of the new society based on epistemological and ontological approaches. The key task of the research made it possible to verify whether "post-globalization" is one of the ways to preserve the life of the globalized world. As a result, the "end of globalization", the world’s entry into a new state under a different name, and the impact of these processes on the individual were confirmed. Meta-ontology has shown, that personality appears as universality in the system of "universe – society – man" relations. It was shown that the new model of society can serve as a basis for the coming world formation. Personality is presented as the basis of a complex system. The proposed model of "Homo Spiritus in Universum Concentus", considering the acceleration of time, is the most optimal in the future.